Questioning Practice and Classroom Interaction - Hieronimus Canggung Darong; Erna Mena Niman; Sebastianus - Menggo; Raimundus Beda (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2021)
Asking question effectively provides insights for teachers to elicit students talk, facilitate students to think and express themselves in classroom interaction.This SOTA aims at reviewing questioning practice as the most common and prominent features of classroom interaction. Besides questioning, the coverage of this review includes classroom interaction practice and teacher talks in the classroom. The final section of the article is the conclusion and suggestion for future research on this topic.